Adsorption kinetics and equilibrium study of nitrogen species onto radiata pine (Pinus radiata) sawdust - Harmayani, K.; Anwar, Faisal (I W A Publishing, 2016)
Nitrogen species (NH3-N, NO3-N, and NO2-N) are found as one of the major dissolved constituents in wastewater or stormwater runoff. In this research, laboratory experiments were conducted to remove these pollutants from the water environment using radiata pine (Pinus radiata) sawdust. A series of batch tests was conducted by varying initial concentration, dosage, particle size, pH, and contact time to check the removal performance. Test results confirmed the effectiveness of radiata pine sawdust for removing these contaminants from the aqueous phase (100% removal of NO3-N, and NO2-N; 55% removal of NH3-N). The adsorbent dosage and initial concentration showed a significantly greater effect on the removal process over pH or particle sizes. The optimum dosage for contaminant removal on a laboratory scale was found to be 12 g. Next, the adsorption kinetics were studied using intraparticle diffusion, liquid-film diffusion, and a pseudo-first order and pseudo-second ordermodel. The adsorption of all species followed a pseudo-second order model but NO2-N adsorption followed both models. In addition, the kinetics of NO2-N adsorption showed two-step adsorption following intraparticle diffusion and liquid-film diffusion. The isotherm study showed that NO3-N and NO2-N adsorption fitted slightly better with the Freundlich model but that NH3-N adsorption followed both Freundlich and Langmuir models.